Housing planning for lower income cities with sustainable development approach in Mehregan township of Mashhad Metropolis - Kar, Mohammad Reza Daime; Ahmadian, Mohammad Ali; Alizadeh, Katayoun; Hataminezhad, Hossein (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Housing is the most important element of the city, which is of great importance in the sustainable development of the city. Therefore, achieving sustainable housing in order to enhance and improve the quality of life of the present and future generations is a major issue. Housing from various perspectives, including architecture, construction of buildings, residential buildings, land and building costs, housing loans, housing market, housing regulations, house prices, Desirable housing, etc., can be considered. On the other hand, housing is the most important concern of the present-day human being and its most important function is economic performance. And its most important function is economic performance. The housing situation and the analysis of housing prices are of particular importance, because the main goal of urbanization is to create human settlements and, among the various uses of urban land, residential use is of particular importance. Also the share of housing is also significant in quantitative term. One of the indicators for measuring poverty is housing. Good and adequate housing is a housing that does not have too much density. And, in many cases, housing and environmental conditions are the most important factor affecting on level of satisfaction of a person in a neighborhood. Apart from the social class and economic conditions of individuals, housing is always one of the most important needs and priorities of the household. The main factors that have led to provide a place to live become a crisis, especially for low-income groups, are: Rapid population growth, a sharp increase in urbanization rates, lower household size, higher rates of profitability of the land market and housing, reduced demand for housing, reduced access rates and poor financial capabilities of the poor, the plummeting market of land and housing to the detriment of low-income groups, the reduction of land and housing supply, the lack of attention of the private sector and, ultimately, unsuccessful government policies. In spite of various experiences to address the problem of disadvantaged low-income groups, the root cause of this problem is the need to examine its structural factors. This paper has been conducted with the purpose of providing a affordable housing pattern for vulnerable urban areas with a sustainable development approach in the Mehregan township of Mashhad Metropolis detachable area using a descriptive-analytical method of applied type. The population of the study is 366 people based on the Cochran formula. Using descriptive and inferential statistics from the completed questionnaires, experts have been analyzed using non-parametric and parametric statistical methods. Since housing is a cross-domain and multidimensional domain, the attitude to it must be all-round and multi-dimensional. Hence, effective policies in the field of housing for low income groups regarding the potential of the marginal areas of Mashhad for system effectiveness will be considered. Finally, in the city of Mehregan, we can solve this problem, By drafting urban planning, architecture and housing construction in accordance with international standards and enhancing their flexibility and encouraging activities in marginalized fabric for the benefit of low income groups and changing the views and plans of urban development projects.